Understanding the State Regulation of Fatherhood in Latin America: Complementary versus Co-responsible - Martínez Franzoni, Juliana (2021)
Fatherhood is a key but missing component of research on welfare regimes. What do states formally demand from fatherhood across Latin America? Using a novel data set of coded legal and policy provisions for 19 Latin American countries, this article offers a conceptual framework to examine state interventions targeting biological, caregiving and breadwinning dimensions of fatherhood. My findings show that, regardless of how robust their social policies are, most countries presume fatherhood to be complementary rather than co-responsible to motherhood. By making a conceptual, empirical and practical contribution to studying the state regulation of fatherhood, this article contributes to a more comprehensive view of welfare regimes.